Kahoot! Application in Medical Education: A Fact for Student Motivation Level - Galuh Suryandari; Alfan Al-Ghifari Sudarmanto (Universitas Muhammadiyah Yogyakarta, 2020)
An implementation and effort of technology in medical education to increase student motivation of the large-scale classes are increasing worldwide. One of them is Kahoot!. This study measured student motivation level in medical school of FKIK UMY after the implementation of Kahoot! Quasi experimental method was implemented in this study. The data was collected by using Motivated Strategies for Learning Questionnaire (MSLQ). During the normality test by using Kolmogorof Smirnov method, all of the data has the amount of p>0,05, therefore we used non parametric analysis with independent sample T-test and one way ANOVA to figure out the relation of student batch and students motivation level. The result showed that only students in batch 2015 who decreased the motivation after implementing Kahoot! Different from students batch 2015, these three batches (2016, 2017, and 2018) increased the motivation after implementing Kahoot!